Adriana Boscaro, Sixteenth Century European Printed Works on the First Japanesse Mission to Europe. A Descriptive Bibliography. E. J. Brill Leiden, 1973. 196 pp. - M. O. M. (El Colegio de México, A.C., 1974)
-